Deadly Drugs and the Doctrine of Double Effect: A Reply to Tully - Masek, Lawrence (Journal of business ethics, 2006)
In a recent contribution to this journal, Patrick Tully criticizes my view that the doctrine of double effect does not prohibit a pharmaceutical company from selling a drug that has potentially fatal side-effects and that does not treat a life-threatening condition. Tully alleges my account is too permissive and makes the doctrine irrelevant to decisions about selling harmful products. In the following paper, I respond to Tully’s objections and show that he misinterprets my position and misstates some elements of the doctrine of double effect. I also show how the doctrine constrains some decisions about marketing drugs with potentially fatal side-effects.